The Implementation of Scientific Approach in Teaching English at SMAN 1 Batukliang Academic Year 2024/2025 - Sulistiani, Salmeinda Maya; Amrullah; Thohir, Lalu (Journal of English Education Forum (JEEF), 2025)
This qualitative descriptive study investigates the implementation of the scientific approach in English language teaching at SMAN 1 Batukliang during the 2024/2025 academic year, with a particular focus on instructional practices and the challenges encountered by teachers. Data were collected through classroom observations, semi-structured interviews, and document analysis involving English teachers from Grades X, XI, and XII. Findings reveal that all participating teachers actively applied the five stages of the scientific approach—observing, questioning, experimenting, associating, and communicating—demonstrating notable creativity in adapting activities to suit their students’ needs. However, consistent challenges emerged across all stages, primarily stemming from students’ limited English proficiency, including insufficient vocabulary, weak grammatical competence, and difficulties in comprehension and oral expression. Additional obstacles included classroom management issues, unequal student participation in group work, and the need for extensive scaffolding and repetition. Despite these hurdles, teachers employed context-sensitive strategies—such as peer monitoring, targeted vocabulary reinforcement, and code-switching—to mitigate barriers and sustain engagement. The study underscores the critical role of teacher agency and pedagogical creativity in navigating the complexities of student-centered learning under Curriculum 2013. It also highlights the necessity of targeted professional development and contextualized support to enhance the effective implementation of the scientific approach in English classrooms.